Saving CeeCee Honeycutt : a novel - Hoffman, Beth (New York : Pamela Dorman Books-Viking, 2010)
Hoffman's debut, a by-the-numbers Southern charmer, recounts 12-year-old Cecelia Rose Honeycutt's recovery from a childhood with her crazy mother, Camille, and cantankerous father, Carl, in 1960s Willoughby, Ohio. After former Southern beauty queen Camille is struck and killed by an ice cream truck, Carl hands over Cecelia to her great-aunt Tootie. Whisked off to a life of privilege in Savannah, Ga., Cecelia makes fast friends with Tootie's cook, Oletta, and gets to know the cadre of eccentric women who flit in and out of Tootie's house, among them racist town gossip Violene Hobbs and worldly, duplicitous Thelma Rae Goodpepper. Aunt Tootie herself is the epitome of goodness, and Oletta is a sage black woman. Unfortunately, any hint of trouble is nipped in the bud before it can provide narrative tension, and Hoffman toys with, but doesn't develop, the idea that Cecelia could inherit her mother's mental problems. Madness, neglect, racism and snobbery slink in the background, but Hoffman remains locked on the sugary promise of a new day.
Keywords: Teenage girls -- Fiction; Families -- Mental health -- Fiction; Eccentrics and eccentricities -- Fiction; Women -- Georgia -- Fiction; Savannah (Ga.) -- Fiction; Domestic fiction